2009
DOI: 10.3122/jabfm.2009.01.080008
|View full text |Cite
|
Sign up to set email alerts
|

Variables Associated With Human Papillomavirus (HPV) Vaccine Acceptance by Men

Abstract: Objective: To determine correlates of human papillomavirus (HPV) vaccine acceptance for men.Methods: A convenience sample of men aged 18 to 45 years read a one-page information sheet about HPV and the HPV vaccine, then completed a 29-item questionnaire.2 tests were used to determine whether differences in demographic, sexual, and vaccine-related variables existed between levels of wanting the HPV vaccine.Results: Positive correlates of HPV vaccine acceptance included higher education (P < .0001); hispanic ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
58
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 24 publications
7
58
1
1
Order By: Relevance
“…16 Not surprising only 4 students in this study have been vaccinated against HPV, but one important observation was that almost 2-thirds were likely to be vaccinated against HPV. This finding was similar to the results observed in the US with values of 67.6% in a group aged 18 to 29, 41 and of 70% in 18-26 y old, 19 higher than the 41% of 16-18 y old college students in England 42 and the 46% in the already mentioned survey in the United Arab Emirates, 34 and lower than the 90.9% among nonhealth sciences students in Portugal. 43 One of the most common reasons for this positive attitude toward the vaccination was that it may reduce the risk of acquiring a HPV infection and this is in accordance with previous surveys 34,42,43 whereas among those who indicated that they do not willingness to get the vaccine, the most frequently mentioned concern was that they were not at risk for the HPV infection.…”
Section: Discussionsupporting
confidence: 77%
“…16 Not surprising only 4 students in this study have been vaccinated against HPV, but one important observation was that almost 2-thirds were likely to be vaccinated against HPV. This finding was similar to the results observed in the US with values of 67.6% in a group aged 18 to 29, 41 and of 70% in 18-26 y old, 19 higher than the 41% of 16-18 y old college students in England 42 and the 46% in the already mentioned survey in the United Arab Emirates, 34 and lower than the 90.9% among nonhealth sciences students in Portugal. 43 One of the most common reasons for this positive attitude toward the vaccination was that it may reduce the risk of acquiring a HPV infection and this is in accordance with previous surveys 34,42,43 whereas among those who indicated that they do not willingness to get the vaccine, the most frequently mentioned concern was that they were not at risk for the HPV infection.…”
Section: Discussionsupporting
confidence: 77%
“…Yet other studies have demonstrated the value of medical advice with respect to HPV vaccine acceptance. 19,21,22 The opinion of a trusted health care provider is particularly important with respect to preventive medical care. The dialogue between parent and health care provider probably has centered around action (getting the vaccine) and not the particular process (voluntary vs mandatory).…”
Section: Discussionmentioning
confidence: 99%
“…, 남학생의 경우도 HPV지식이 낮았 으며, 지식은 백신접종의도와 상관성을 보이고 있었다 (Ferris et al 2009;Katz et al, 2011;Wheldon et al, 2011). …”
unclassified